2006
DOI: 10.1590/s1415-47572006000400016
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous microsatellite primer pairs informative for the whole genus Arachis

Abstract: The genus Arachis currently comprises 69 described species, some of which have potential and real value as human and animal foods. These Arachis species have been collected and maintained in germplasm banks to provide material that can be used as sources of genes in breeding programs and for the selection of new cultivars. One of the principal objectives of germplasm conservation is the evaluation of genetic variability, which is best conducted using molecular markers. We investigated the use of heterologous p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
(14 reference statements)
3
17
0
2
Order By: Relevance
“…The microsatellite primer pairs used were developed for A. hypogaea (Ferguson et al, 2004). The transferability of microsatellite primers was high, as observed in many other studies on Arachis species Hoshino et al, 2006;Moretzsohn et al, 2009;Koppolu et al, 2010).…”
Section: Hybridization and Hybrid Identificationmentioning
confidence: 78%
“…The microsatellite primer pairs used were developed for A. hypogaea (Ferguson et al, 2004). The transferability of microsatellite primers was high, as observed in many other studies on Arachis species Hoshino et al, 2006;Moretzsohn et al, 2009;Koppolu et al, 2010).…”
Section: Hybridization and Hybrid Identificationmentioning
confidence: 78%
“…For example, in an interspecific analysis, Hoshino et al (2006) evaluated 76 accessions of 34 species from nine Arachis sections and showed that this germplasm bank possessed high variability, even when a species was represented by few accessions. This information was used to maintain Arachis genetic diversity during the storage and conservation process.…”
Section: Genetic Diversity and Individual Identificationmentioning
confidence: 99%
“…Para superar essas limitações, alguns autores aumentaram o número de iniciadores utilizados (Dwivedi et al, 2001;Raina et al, 2001), analisaram acessos de diferentes variedades botânicas (Subramanian et al, 2000;Raina et al, 2001) e, mais recentemente, iniciadores microssatélites têm sido desenvolvidos e utilizados em estudos de diversidade genética, em várias espécies do gênero Arachis (Hopkins et al, 1999;He et al, 2003He et al, , 2005Ferguson et al, 2004;Moretzsohn et al, 2004Moretzsohn et al, , 2005Palmieri et al, 2005;Bravo et al, 2006;Hoshino et al, 2006 …”
Section: Resultsunclassified
“…A espécie A. hypogaea é classificada conforme a ausência ou a presença de flores no eixo principal em duas subespécies, hypogaea e fastigiata, respectivamente, divididas em seis variedades botânicas, conforme o hábito de crescimento -subespécie hypogaea: hypogaea e hirsuta; subespécie fastigiata: fastigiata, vulgaris, aequatoriana e peruviana (Krapovickas & Gregory, 1994). O amendoim também é classificado agronomicamente, conforme caracteres vegetativos e reprodutivos, como pertencente aos grupos Valência (A. hypogaea subsp.…”
Section: Introductionunclassified